Dead even - Meltzer, Brad (Rob Weisbach Books, 1998)
Lawyer Jared Lynch of New York is warned he will be killed if he fails to successfully defend his client, a criminal. Lynch could ask his wife to lose as she is the prosecutor in the case, but professional pride prevents him and he says nothing.